Penilaian Status Kesuburan Tanah Pada Kawasan Hutan di Kecamatan Wonosalam Kabupaten Jombang - Assabil, Fadli Fikri; Santoso, Setyo Budi; Siswanto, Siswanto (Jurnal Solum, 2023)
Wonosalam is one of the sub-districts in Jombang Regency. Various forms of land use exist in Wonosalam Subdistrict, one of which is forest area, Forest is a valuable natural resource, because it provides great benefits for human welfare. The aim of the study was to assess the fertility status and management reference on several forest land uses in Wonosalam sub-district. The study used a land survey method, soil samples were taken purposively (purposive sampling) at depths of 0-20 and 20-40 obtained 4 composite sampling points. Soil chemistry table was used to determine the value and criteria of soil chemistry. Stages of research with soil analysis using five soil fertility parameters (CEC, base saturation, C-organic, P-available and K-available), which are used to assess the state of soil fertility. The results showed that fertility was low at all sampling points due to limiting factors of C-organic concentration and alkali saturation.Keywords: fertility, forest, soil, wonosalam